Silver Recovery Method from Radiographic and X- Ray Film Waste- A Review - Shaker Salih Bahar; Sata Kathum Ajjam; Ahmed Al-Salman; Haneen Zuhair Naji; Hayfaa A.Mubarak (Zien Journals, 2023)
The current study describes a simple and efficient method for recovering silver from waste x-ray film by employing sodium hydroxide and sodium sulfide. The principal sources of silver for silver recovery in this article are X-ray film effluent and radiographic waste. Environmental concerns are driving increased attempts to recover, regenerate, and recycle radioactive waste. Though not as hazardous as other soluble salts, soluble salt and emissions from the recovery process are severely damaging to the environment. Highpurity products can be generated with low waste thanks to hydrometallurgical procedures such as chemical precipitation and adsorption. Silver recovery using oxalic acid chemical precipitation has been offered as a study topic.
Keywords: Hydrometallurgy; X-Ray film; Radiographic waste